Beyond databases, architectures and structures : facing the challenges of data proliferation and growing variety : 14th International Conference, BDAS 2018, held at the 24th IFIP World Computer Congress, WCC 2018, Poznan, Poland, September 18-20, 2018, Proceedings /: facing the challenges of data proliferation and growing variety : 14th International Conference, BDAS 2018, held at the 24th IFIP World Computer Congress, WCC 2018, Poznan, Poland, September 18-20, 2018, Proceedings. (2018) - Unknown
No abstract available